Adult and youth Literacy : National, regional and global trends 1985 - 2015 - UNESCO, Institute for Statistics (UIS Information Paper, 2013)
This document presents data by the UNESCO Institute for Statistics (UIS) on adult and youth literacy in 151 countries and territories from eight regions: Arab States, Central Asia, Central and Eastern Europe, East Asia and the Pacific, Latin America and the Caribbean, North America and Western Europe, South and West Asia, and sub-Saharan Africa. The document summarises the most recent literacy rates and estimates of the illiterate population, and presents historical trends since 1985 and prospects for 2015. For 18 countries, data based on an assessment of reading skills are provided. The analysis is accompanied by a description of UIS methodology in the field of literacy statistics, including the definition of literacy, data sources and calculation methods. A statistical annex contains six tables and 151 figures with literacy data.
Keywords: éducation; enseignement; literacy; littératie